Asian Yearbook of International Law, Volume 1 (1991) - Swan, Sik Ko; Syatauw, J.J.G; Pinto, M.C.W (Brill | Nijhoff, 1993)
The Asian Yearbook of International Law is the first publication primarily dedicated to international law as seen from an Asian perspective. It provides a forum for the publication of articles in the field of international law written by experts from the region, and also other articles relating to Asian topics. Its aim is twofold: to promote the dissemination of knowledge of international law in Asia and to provide an insight into Asian views and practices, which will be especially useful to a non-Asian readership. As a rule, each volume of the Asian Yearbook will contain Articles, Notes, State Practice, a Chronicle of Events and Incidents, United Nations Activities with Special Relevance to Asia, a Survey of Activities of the Asian-African Legal Consultative Committee, a Bibliography and a Documents section.
Keywords: International law -- Asia -- Periodicals.; International law; Asia; Public international law; Periodicals